DETERMINATION OF ACCEPTABLE VALUES OF THE MAIN FACTORS AFFECTING THE PRODUCTION OF TWISTED THREAD - Atambayev, Dinmuhammad; Xaydarov, Umarjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
In this article, the limit parameters of the main factors affecting the performance of the improved working part of the yarn winding machine were determined, and their optimal values were determined by the method of mathematical planning. These values were graphed and analyzed for the effect of the machine on yarn stiffness.